MITOLOGI ANAK-ANAK ALLAH DI DALAM KEJADIAN 6:2 - Oky Otto Otto (STT BIBLIKA JAKARTA, 2020)
Bible interpretation always develops with hermenutics methods and historical proofs. For a theologian difficult text is a challenge to find the meaning reffered by the text. Interpretation about who is the childrens of God in Genesis 6:2 dan their descendants would be interesting to study. The right interpretation will confirm Christian doctrines and help the spiritual life application for the believers. A qualitative method approached with historical-gramatical interpretation method applied to studi who were sons of God in Genesis 6:2 and the impact in humanity descendants on earth. Ancient literatures around Near East world will give contribution to understand the cultures at that time and knowledges about sons of God in Moses’s writing. The conclusion is that there was no hybrid descendants generated from marriaged between human with fallen angels.